CHALLENGES IN QUALITY OF EDUCATION IN HIGHER EDUCATION INSTITUTIONS (HEIS) OF PAKISTAN - Zohaib Hassan Sain (Jurnal Ilmiah Manajemen & Bisnis, 2022)
The reason for this research is based on formulative research to recognize “Challenges in Quality of Education in HEIs of Pakistan”. Formulative research method is used to execute the goals of the research in less time and inexpensive means. In the past few years, education sector is Pakistan is confronting a lot of provocations in education sector such as: curriculum, less training institutions, corruption in education, teacher’s behavior, less research work. Coming-up concerns in the education sector are less training institutions and less research work and research is necessary to follow for the progress and power of any economy. The aim of our study is to recognize the important challenges which is being suffered by the academic sector in Pakistan the past few years. In order to carry the reliability and validity of the data for results, the researcher has used triangulation. The researcher has used questionnaire for students, questionnaire for teachers and interviews of the management in order to conduct this triangulation. The primary data was gathered from the focused group of students using a sample of 100 questionnaires for each university were filled by the students of the selected five universities. This attempt of conducting the research will play an essential part in the progress of Pakistan. In this study the dependent variables are: Curriculum, Corruption in education, less training institutions, Teacher’s behavior, less research work and dependent variable is Quality of Education. For future research, study can be done on solutions of these problems. In order to improve the literacy rate, the government of Pakistan has stated that education is mandatory for each and every citizen in the country.